Micromechanics modeling of magneto-sensitive polymeric materials during curing - Chatzigeorgiou, George; Mokarram, Hossain; Meraghni, Fodil; Steinmann, Paul (ICCM International Conferences on Composite Materials, 2015)
This work proposes a coupled magneto-mechanical multi-scale model for simulating the curing process of magneto-sensitive polymers. In this type of composites, ferromagnetic particles are mixed with a liquid polymeric matrix in the uncured stage. The polymer curing process is a complex mechanism that transforms a fluid to a solid with time. In order to identify the overall response of the magneto-mechanically coupled polymeric composite, an extended Mori-Tanaka semi-analytical homogenization procedure is utilized that tranfers information from the micro to the macroscale. The stiffness gaining phenomenon as in the case of a curing process is realized by time-dependent material parameters appearing within the polymer piezomagnetic material tensors. Moreover, the volume reduction during curing is taken into account through a magnetic induction dependent shrinkage model. Several numerical examples illustrate the model capability to capture major observable phenomena in the curing process of polymeric composites under infinitesimal deformations and magnetic field.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Curing; Magneto-mechanics; Magneto-sensitive polymers; Mori-Tanaka; Shrinkage